Je ucho podzemních hlodavců skupiny Hystricomorpha specializované na podzemní prostředí? - Koucká, Anna (Jihočeská univerzita, 2022)
The aim of this work is to develop a review on the morphology of the auditory system in rodents with different levels of underground activity, to compare the morphology within the group Hystricomorpha and to evaluate whether the auditory system in some rodents of this group is specialized in the underground environment.
Is the ear of subterranean rodents of Hysticomorpha specialized to the underground environment?
Keywords: Rodentia; Hystricomorpha; ear structure; middle ear; subterranean; fossorial; Rodentia; Hystricomorpha; ear structure; middle ear; subterranean; fossorial